Poligami dalam Pandangan Hukum Islam (Kritik terhadap Larangan Poligami dalam UU Turki) - Muspiroh Muspiroh (Journal on Education, 2023)
Polygamy has become one of the most interesting issues in Turkey by establishing legislation in force in the Muslim country regarding threats and punishment for polygamy perpetrators, because fundamentally Islamic law has never stipulated the prohibition of polygamy. Only a few contemporary Muslim thinkers, through ijtihadi interpretations, forbid polygamy today. Referring to the literal meaning of the Koran, every Muslim man can marry up to four women, on condition that they act fairly. In the legislation of the Turkish State, polygamy is a practice that is considered to violate the laws in force in that country, Turkey believes that the negative effects are very large for families and hurt women a lot. So that in this case Turkey prohibits polygamy for its people and will provide criminal sanctions for anyone who violates these rules.